2019
DOI: 10.1177/1757975919854045
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing an HIV community advisory board as an agent of community action and health promotion in a low-resource setting: a case-study from Nova Iguaçu, Rio de Janeiro, Brazil

Abstract: Introduction: Brazil’s HIV burden has greatly increased over the past decade, especially for socially marginalized and vulnerable groups such as adolescents, women, and men who have sex with men. The reasoning for worsening HIV outcomes is complex, but ongoing economic and political crises have placed extreme operational and financial burdens on both the public health system and HIV-related civil society, affecting both treatment and prevention efforts and delivery. Context: Community-based HIV-related health-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, the comparative analysis by sociodemographic variables showed signi cant increases for younger age groups (18-24 and 25-34 years), for MSM, and for those who do not live with a partner. These results show a greater awareness concerning HIV risk exposure in the most at risk population groups, suggesting that prevention actions focused on key populations have been successful (32).…”
Section: Discussionmentioning
confidence: 77%
“…However, the comparative analysis by sociodemographic variables showed signi cant increases for younger age groups (18-24 and 25-34 years), for MSM, and for those who do not live with a partner. These results show a greater awareness concerning HIV risk exposure in the most at risk population groups, suggesting that prevention actions focused on key populations have been successful (32).…”
Section: Discussionmentioning
confidence: 77%
“…Identifying factors associated with the nondisclosure of sexual orientation is crucial for the development of interventions to strengthen protection from stigma and discrimination, as well as improve healthcare access among MSM. A survey in Germany showed that respondents who had never tested for HIV were more likely to live in a city with less than 100,000 inhabitants and to be less open about their sexual orientation to their primary care provider [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This model is predominantly used when a research team has a specific project or linked set of projects they are planning, thereby making it a popular choice for ESIs and graduate students, whose resources might also be limited to that specific project. Examples of a population-specific model of CABs in the context of HIV-related research include high incidence substance using populations in major metropolitan areas, 40 people living with HIV in an international low-resource setting, 22 or Latino sexual minority men in a US HIV epicenter (current CAB in partnership with first and senior authors). CABs operating within this model are often composed of members primarily from the subpopulation of interest and focused on strengthening existing protocols rather than anticipating future research projects.…”
Section: Overview Of Cab Formation Guidelinesmentioning
confidence: 99%
“…Oswaldo Cruz Foundation and General Hospital of Nova Iguaçu Brazil. 22 Low-resourced communities in Rio de Janeiro, Brazil.…”
Section: Establishment: Practical Examples Of Cab Responsibilitiesmentioning
confidence: 99%